Evaluation And Analysis Of Application Of The Scrum Method To Increase The Success Of Go-Live Phase In Sap Analytics Cloud Dashboard Implementation Projects (Case Study Of Mining Owner & Mining Contractor Industry) - Sabil Nararya; Lukman Abdurrahman; Basuki Rahmad (UNIVERSITAS PAKUAN, 2025)
To evaluate the company's business development carried out by the Board of Directors, an ERP dashboard system is needed that can provide information on business development in real time. So it takes the implementation of the SAP Analytics Cloud Dashboard system. However, company stakeholders engaged in the mining owner and mining contractor sector want the project to be monitored in every process. So that if there are errors or changes in the process of making a report on the dashboard, then this can be known earlier and changed as needed. Seeing the conditions of this need, a company engaged in consulting as a solution management service provider that initially proposed using the ASAP method, otherwise known as Accelerated SAP, is proposing to change the project method to the scrum method in the SAP Analytics Cloud implementation project in companies engaged in the mining owner and mining contractor industry. This research was conducted with the limitations and objectives to evaluate and analyze the effect of the application of the scrum method on the SAP Analytics Cloud Dashboard implementation project in increasing the success of the go-live phase of the project.